In vitro evaluation of the efficiency of Ocimum gratissimum oil and ferulic acid in controlling the development of dental plaque and calculus in dogs (Research, Society and Development, 2022)
Dental plaque and calculus are two of the most common diseases in small animal veterinary practice. They promote de accumulation of bacteria on the surface of canine teeth, which is also the main cause of periodontal disease. Periodontal disease destroys the tissue that supports the teeth and when left untreated can have systemic repercussions. Daily brushing of the dog´s teeth is the most effective method of preventing these afflictions, but that is still not a reality for most owners and many of the products available on the market for that purpose have negative long term effects for the pacient´s health. With that being said, this project sought to test the efficiency of Ocimum gratissimum oil and ferulic acid, main component of brown propolis extract, in combatting the bacteria that produces dental plaque and calculus, introducing a less aggressive option for the treatment of these diseases. In order to do so, 14 samples of plaque and calculus were collected from dogs of different ages, sex and breeds; the microrganisms present in those samples were identified and agar diffusion tests and evaluation of inhibition halo diameters were performed for each treatment of interest. The study showed that the most efficient treatments were the Ocimum gratissimum oil as well as its association with ferulic acid and an existent commercial propolis based gel, both having had equivalent results.